Longitudinal intravital imaging of the femoral bone marrow reveals plasticity within marrow vasculature - David Reismann (Nature Portfolio, 2017)
Longitudinal imaging of bone marrow would shed insight into long-term cellular dynamics within this compartment. Here, the authors develop a multi-photon imaging approach for the mouse femur and reveal extensive vascular plasticity within the bone marrow during bone healing and steady-state homeostasis.